IMPLEMENTASI KEBIJAKAN PENGHAPUSAN BENTUK-BENTUK PEKERJAAN TERBURUK UNTUK ANAK (PBPTA) PADA PEKERJA RUMAH TANGGA ANAK DI KOTA SEMARANG - Maulida Putri Rahmawati; Diah Hariani; Ari Subowo (Journal of Public Policy and Management Review, 2013)
This research explain to know how the implementation of elimination of the worst forms of child labour especially for Child Domestic Labour in Semarang. There is child labour in domestic, this job classified to be abolished job by the government incorporated in the Action Committee for the Establishment of Districts / Municipalities based in Semarang Mayor Decree No. 560.05/256 on the establishment of the Committee Action for the Elimination Worst Forms of Child. In research method, the author used policy implementation theory by Meriiee S. Grindle consist of two variable they are content of policies (content) and environmental policy (contex). The data collection conducted from Manpower and Transmigration Department, Empowerment Entities, Women and Family Planning, Merdeka Domestic Union Semarang and Child Labour. There are many findings actual Policy Implementation Elimination of the Worst Forms of Child in Semarang, constrained by limited human resource capacity as stakeholders, lack of coordination, there is still weak sanctions for those who violate it provides, offers and take advantage of children for the exploitation.